Internal jugular vein blood flow in multiple sclerosis patients and matched controls. - Marcello Mancini; Roberta Lanzillo; Raffaele Liuzzi; Orlando Di Donato; Monica Ragucci; Serena Monti; Elena Salvatore; Vincenzo Brescia Morra; Marco Salvatore (PLoS ONE)
The aim of the study was to investigate the Internal Jugular Veins dynamics using contrast enhanced ultrasonography in Multiple Sclerosis patients, clinically isolated syndrome patients and healthy controls. Contrast enhanced ultrasonography imaging of the Internal Jugular Vein was performed in fifty-eight patients with Multiple Sclerosis, seven clinically isolated syndrome patients and in thirteen healthy controls. Time-intensity curves were quantified using a semi-automated method and compared with clinical disease outcomes. Wash-out parameters were calculated and six Time-intensity curves shapes were created. Significantly reduction of wash-out rate in Internal Jugular Veins was detected in Multiple Sclerosis patients compared to healthy controls [22.2% (2.7%-65.9%) vs. 33.4% (16.2%-76.8%); P<0.005]. Internal Jugular Vein enhancement was heterogeneous in patients with Multiple Sclerosis and consisted of slow wash-out Time-intensity curves shapes, compared with almost only one type of Time-intensity curves shape in control subjects that correspond to fast enhancement and fast wash-out. The vein wash-in parameters were similar in Multiple Sclerosis group compared with controls. A significant correlation was found between Internal Jugular Vein wash-out and level of disability (R =  -0.402, p<0.05). Contrast enhanced ultrasonography of the Internal Jugular Vein with time intensity curve analysis revealed alterations of cerebral venous outflow in Multiple Sclerosis patients, however mechanisms that determine this condition remains unclear.